ETIOLOGY, PATHOPHYSIOLOGY, CLINICAL MANIFESTATIONS, THERAPEUTIC INTERVENTIONS, AND SCREENING STRATEGIES FOR HYPOTHYROID DISORDERS AND INNATE HYPOTHYROIDISM - ISKANDAROVA FATIMA IBADULLAYEVNA, (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
Hypothyroidism, encompassing both acquired and congenital forms, remains a prevalent endocrine disorder characterized by thyroid hormone deficiency, with significant implications for global health. This thesis reviews the etiopathogenesis, clinical manifestations, treatment strategies, and screening protocols for hypothyroidism syndrome and congenital hypothyroidism (CH), emphasizing recent advances from 2024-2026. Etiopathogenesis highlights autoimmune processes, iodine deficiency, and genetic mutations as primary causes, while clinical courses vary from subclinical to overt symptoms affecting multiple systems. Treatment predominantly involves levothyroxine (L-T4) replacement, with guidelines advocating early intervention to mitigate neurodevelopmental risks in CH. Screening programs, particularly newborn screening (NBS), have evolved with optimized TSH cut-offs and machine learning integration to enhance detection accuracy. Drawing on high-impact literature, this work underscores the need for multidisciplinary management and future research into cell-based therapies and expanded screening for rare thyroid disorders.